2004
DOI: 10.1016/j.synthmet.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting ambipolar organic heterostructure field-effect transistor

Abstract: We have investigated ambipolar charge injection and transport in organic field-effect transistors (OFETs) as prerequisites for a lightemitting organic field-effect transistor (LEOFET). OFETs containing a single material as active layer generally function either as a p-or an n-channel device. Therefore, ambipolar device operation over a wide range of operating voltages is difficult to realize. Here, we present a highly asymmetric heterostructure OFET architecture using the hole transport material pentacene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 24 publications
0
46
1
Order By: Relevance
“…20 At a certain drain voltage, the electron current in the n-type material at the p-n interface is equal to the hole current in the p-type material. In contrast to previously published LEOFETs, 15,16,19 increasing |V D | beyond this voltage leads to a saturation of the current. This is explained by the fact that a further increase of |V D | does not lead to an increase of the hole current.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…20 At a certain drain voltage, the electron current in the n-type material at the p-n interface is equal to the hole current in the p-type material. In contrast to previously published LEOFETs, 15,16,19 increasing |V D | beyond this voltage leads to a saturation of the current. This is explained by the fact that a further increase of |V D | does not lead to an increase of the hole current.…”
Section: Resultscontrasting
confidence: 92%
“…12,13 Rost et al reported on a LEOFET in which the active layer was formed by a heterostructure of a ptype and an n-type organic semiconductor, either by coevaporation 14 or by subsequent evaporation of both semiconductors. 15 The presence of an n-type and p-type semiconductor is a clear advantage in comparison to tetracene-based p-type-only LEOFETs. However, as neither of the semiconductors is patterned, there is little control over the position in the channel where the light is emitted.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Only recently light emission from within the transistor channel was demonstrated in ambipolar OFETs (i.e., capable of transporting both holes and electrons). [9][10][11][12][13][14] In an ambipolar LEOFET when the gate is biased in between the source and drain potentials, holes and electrons are injected simultaneously at the opposite ends of the channel. At the point where the local potential within the channel equals the gate potential a pn-junction is formed at which opposite carriers can recombine to form excitons.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Due to this unique combination of properties, LEFETs have potential applications in the fabrication of simplified pixels for flat panel displays, optical communication devices, and electrically driven organic lasers. [12][13][14][15][16] Injection and transport of both electrons and holes are important requirements for generating electroluminescence in LEFETs.…”
mentioning
confidence: 99%